Comparative pharmacoeconomic assessment of apixaban vs. standard of care for the prevention of stroke in Italian atrial fibrillation patients - Lorenzo Pradelli; Mario Calandriello; Roberto Di Virgilio; Marco Bellone; Marco Tubaro (Farmeconomia: Health Economics and Therapeutic Pathways, 2014)
OBJECTIVES: The aim of this study was to evaluate the cost‑effectiveness of apixaban in the prevention of thromboembolic events in patients with non‑valvular atrial fibrillation (NVAF) relatively to standard of care (warfarin or aspirin) from the Italian National Health System (SSN) perspective. METHODS: A previously published lifetime Markov model was adapted for Italian context. Clinical effectiveness data were acquired from head‑to‑head randomized trials (ARISTOTLE and AVERROES); main events considered in the model were ischemic and hemorrhagic stroke, systemic thromboembolism, bleeds (both major and clinically relevant minor) and cardiovascular hospitalizations, besides treatment discontinuations. Expected survival was projected beyond trial duration using national mortality data adjusted for individual clinical risks and adjusted by utility weights for health states acquired from literature. Unit costs were collected from published Italian sources and actualized to 2013. Costs and health gains accruing after the first year were discounted at an annual 3.5% rate. The primary outcome measure of the economic evaluation was the incremental cost effectiveness ratio (ICER), where effectiveness is measured in terms of life‑years and quality adjusted life‑years gained. Deterministic and probabilistic sensitivity analyses (PSA) were carried out to assess the effect of input uncertainty. RESULTS: Apixaban is expected to reduce the incidence of ischemic events relative to aspirin and to improve bleeding safety profile when compared to warfarin. Incremental LYs (0.31/0.19), QALYs (0.28/0.20), and costs (1,932/1,104) are predicted with the use of apixaban relative to aspirin and warfarin, respectively. The ICERs of apixaban were € 6,794 and € 5,607 per QALY gained, respectively. In PSA, the probability of apixaban being cost effective relative to aspirin and warfarin was 95% and 93%, respectively, for a WTP threshold of € 20,000 per QALY gained. Univariate analyses indicate that results were most sensitive to variations of the absolute risk reduction for cardiovascular events with apixaban. CONCLUSIONS: Apixaban is expected to increase life expectancy and quality‑adjusted life expectancy, but also costs dedicated to Italian NVAF patients, as compared to standard of care. The resulting ICERs have high probabilities of being below the conventional thresholds of WTP for health benefits of the SSN, indicating efficient allocation of health care resources.